Prinsip-prinsip Pendidikan dalam Perspektif Al-Qur’an dan Hadist - Anshory, Muhammad Isa; Muharromah, Fityatul; Fani, Farid Al (Lembaga Yasin AlSys, 2025)
Education is a fundamental aspect in the formation of individual and societal character. Educational principles based on the Koran and Hadith provide comprehensive instruction that covers spiritual, moral, intellectual and social aspects. The purpose of this article is to examine educational principles from the perspective of the Al-Quran and Hadith using literature review and textual analysis methods. The Koran emphasizes the importance of knowledge, the formation of noble morals, and balance between this world and the afterlife. The hadith of the Prophet Muhammad (saw) emphasizes the need for example, motivation and compassion in the educational process. The findings of this research indicate that the principles of Islamic education focus on realizing full human potential with the aim of achieving happiness in life in this world and the hereafter. This article aims to be a reference in curriculum development and teaching practices based on Islamic values.